A Case Study on the Ayurvedic Approach to Managing Psoriasis (Ek Kustha) (International Journal of Ayurveda and Pharma Research, 2024)
Ek-Kushta is similar to psoriasis. In the present era, this disease remains a matter of serious concern. These symptoms can be compared to Ek-Kushta. The digestive fire Agni also get Manda consuming red meat, non-veg food and drinks are more prone to get skin diseases like psoriasis or many auto immune disorders. The skin disease was referenced in the Kushta chapter of Charaka Samhita, along with other Samhitas, in our classical texts. For this many different Chikitsas like Shodana shaman, Virechana etc are explained in our classics. Here, a traditional Ayurvedic regimen was attempted to treat a 20 year old male. Methods: Samshodhana with Samshamana medication are the treatment for all varieties of Kushta. In this study, Virechana was administered first, followed by Samshamana medicine. Results: The evaluation of signs and symptoms was conducted prior to the commencement of treatment and subsequently after the completion of treatment. Following 4 weeks of scaling treatment, there was a reduction in the thickness of the skin, which had a sharply defined margin, was indurated, and presented as an erythematous plaque on the scalp, face, chest, abdomen, whole back, upper and lower limbs. Significant improvement in psychological and social behavior, which improved the quality of life of patients. After 4 weeks of treatment, the results of the Positive Auspitz's and candle grease sign were found to be negative. Conclusion: Virechana and Samshamana is effective in the management of Ek-Kushta (Psoriasis). After 4 weeks of observation, it appears Virechana and Samshamana can be used to decrease disease progression.